2008
DOI: 10.1111/j.1479-8298.2008.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Number and size of clutch in Ptomascopus morio (Coleoptera: Silphidae: Nicrophorinae), with comparisons to Nicrophorus

Abstract: Ptomascopus morio displays simpler parental care than Nicrophorus species. The effects of carcass size and clutch number on clutch size in P. morio were examined. Clutch size was related to carcass size. There was a negative correlation between number of clutch and clutch size for most sizes of carcass. Longevity of females was shorter when the carcass size was larger, such that total lifetime fecundity did not differ among carcasses of different sizes. The clutch size of P. morio was larger than that of Nicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…quadripunctatus , which breeds predominantly from April to May and September to October, but it may not have been for Ni. concolor , which breeds predominantly from July to September, with a peak in August (Nagano & Suzuki, 2003b ). Therefore, to evaluate the effect of DMDS and DMTS on the attraction of Nicrophorus beetles, further experiments that consider the breeding season and use actual carcasses supplemented with DMDS and DMTS individually, as in Trumbo and Dicapua ( 2021 ), are needed.…”
Section: Discussionmentioning
confidence: 99%
“…quadripunctatus , which breeds predominantly from April to May and September to October, but it may not have been for Ni. concolor , which breeds predominantly from July to September, with a peak in August (Nagano & Suzuki, 2003b ). Therefore, to evaluate the effect of DMDS and DMTS on the attraction of Nicrophorus beetles, further experiments that consider the breeding season and use actual carcasses supplemented with DMDS and DMTS individually, as in Trumbo and Dicapua ( 2021 ), are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The authors interpreted this result as consistent with the ‘semelparity hypothesis’, in that iteroparity was associated with lower levels of maternal care. In another study, Nagano and Suzuki () compared maternal investment in future reproduction between two species of Nicrophorine beetles: Nicrophorus quadripunctatus , which displays more elaborate parental care (carcass preparation, offspring attendance and provisioning); and Ptomascopus morio , which displays simpler parental care (offspring attendance only). In contrast to predictions of the ‘semelparity hypothesis’, the authors found that Nicrophorus quadripunctatus can oviposit several times in one breeding season and that they regulate their clutch size more strictly than P. morio .…”
Section: Ecology Life History and Insect Parental Carementioning
confidence: 99%